The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s10571-018-0599-0
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Promotes BDNF Expression of N2a Cells via Inhibition of miR-155-Mediated Repression After Oxygen-Glucose Deprivation and Reoxygenation

Abstract: Minocycline, an anti-infective agent of a tetracycline derivative, is reported to improve behavioral functional recovery after cerebral ischemia via enhancing the levels of brain-derived neurotrophic factor (BDNF). However, the precise mechanisms that minocycline targets to enhance the expression of BDNF are not fully defined. In the present study, we observed the neuroprotective effect and its potential mechanisms of minocycline using oxygen-glucose deprivation/reoxygenation (OGD/R)-treated N2a cells. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
2
14
0
1
Order By: Relevance
“…Quantitative real-time polymerase chain reaction (qRT-PCR) was performed as previously described [24].…”
Section: Quantitative Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…Quantitative real-time polymerase chain reaction (qRT-PCR) was performed as previously described [24].…”
Section: Quantitative Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…Minocycline inhibits caspase 1 (the proIL-1β-converting enzyme) (Sanchez Mejia et al, 2001), reduces cyclooxygenase-2 expression, prostaglandin E2 production (Yrjanheikki et al, 1999) and inducible nitric oxide synthase up-regulation (Yrjanheikki et al, 1998). Its use therefore inhibits immunological pathways including decreases in interleukin-1β and TNF-α (Afshari et al, 2018; Aparicio et al, 2018), or an increased expression ratio of Bcl-2/Bax and reduced expression of caspase-3 by the modulation of miR-155-mediated BDNF repression (Lu et al, 2018), an inflammatory and immune response regulator (Song and Lee, 2015). It was also suggested that it decreases the levels of toll-like receptor 2 (TLR2) content, and its adapter protein MyD88, as well as the levels of the protein NLRP3, which is indispensable in the composition of inflammasome (Garcez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Other miRNAs are also potentially associated with stroke. For instance, miR-124, miR-210, miR-10b-5p, and miR-155 were shown to directly target BDNF [ 27 , 28 , 30 , 31 ]. Numerous studies have reported that the expression levels of BDNF in rat brain tissue surrounding the haematoma, the cerebral cortex, the peri-infract cortex, the subventricular zone, the striatum, the hippocampus, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in MCAO brain tissues, bioinformatic analysis showed that miR-10b-5p could bind directly to the 3′-UTR sites of BDNF and negatively regulate its expression [ 30 ]. In a recent study, miR-155 targeted BDNF, and downregulation of miR-155-targeted BDNF transcripts protected against ischaemic brain injury [ 31 ]. Another study reported a similar conclusion: miR-155, miR-1, miR-10b, and miR-191 directly repressed BDNF by binding to their predicted sites in the 3′-UTR of BDNF [ 32 ].…”
Section: Main Textmentioning
confidence: 99%